HPV‐vaccination and cancer cervical screening in 53 WHO European Countries: An update on prevention programs according to income level. (16th April 2019) - Altobelli, Emma; Rapacchietta, Leonardo; Profeta, Valerio F.; Fagnano, Roberto
Abstract: Human papillomavirus (HPV) is the most common sexually transmitted disease in the world. The aim of our study is to describe the differences in HPV‐vaccination coverage and screening programs in WHO European Countries notably according to income levels. Multiple correspondence analysis was applied to examine the association among the following variables: Gross National Income (GNI) levels (Lower‐Middle Income, LMI; Upper‐Middle Income, UMI; and High Income, HI); type of CC screening program (coverage; opportunistic/organized); vaccination payment policies (free or partial or total charge); mortality rates/100 000 (≤3; >3‐6; >6‐9; >9); incidence rates/100 000 (≤7; >7‐15; >15‐21; >21). Data HPV‐vaccination start (years) (2006‐2008; 2009‐2011; 2012‐2014; >2014; no program); coverage HPV‐vaccination percentage (≤25; 26‐50; 51‐75; >75); data screening start (years) (<1960; 1960‐1980; 1981‐2000; >2000); primary screening test (HPV, cytology), and screening coverage percentage (≤25; >25‐50; >50‐75; >75). A high income is associated with: start of screening before 1960, medium‐high screening coverage, organized screening, start of vaccination in the periods 2009‐2011 and 2012‐2014 and high immunization coverage. On the other hand, lower‐middle income is associated with: late start of vaccination and screening programs with cytology as primary test, high mortality and incidence rates and lower‐medium vaccination coverage. Our results show a useful scenario for crucial support to public health decision‐makers. Public health authorities should monitor the HPV‐vaccinated population in order to determine more precisely the effects on short‐ and long‐term incidence and mortality rates. In fact, the greater the vaccination coverage, the greater will be the efficacy of the program for the prevention of CC and other HPV‐related diseases. Abstract : Countries with high income, adopting vaccination and screening programs, have low incidence and mortality rates respect to those with lower‐middle income. Eastern European and Asian Countries have lower‐middle income and show high incidence and mortality rates, indicating poor attention to prevention (primary and secondary).